Perseveration and over-switching in schizophrenia - Yogev, Herzel; Hadar, Uri; Gutman, Yaakov; Sirota, Pinkhas (Schizophrenia research, 2003)
Perseveration and switching in positive and negative schizophrenic patients are usually seen as manifestations of attention disorders. They may be closely related to each other, but have not been investigated in an integrated fashion. Such integrated investigation could contribute to the neurophysiological understanding of the relationship between the regional and the pharmacological deficit in schizophrenia. This study has developed a new tool—the Combined Attention Test (CAT)—for the simultaneous measuring of perseveration and switching. Forty-one unmedicated schizophrenic patients were tested. Using the Positive and Negative Sorting Scale (PANSS), subjects were classified into the two experimental groups: positive and negative schizophrenics. The control group consisted of 24 healthy subjects. Schizophrenic patients with positive symptoms tended to switch more than schizophrenic patients with negative symptoms and normal subjects; schizophrenic patients with negative symptoms tended to perseverate more than schizophrenic patients with positive symptoms and normal subjects. Over-switching is discussed as a specific symptom related to positive schizophrenia.